Antibacterial activity of ethanol extract of Sargassum polycystum against Streptococcus mutans and Lactobacillus casei: in vitro - Ab. Halim, Noorhazayti; Zakaria, Nurul Syahidah; Md Hisham, Sarah Shafinaz; Husain, Juzaily; Md Mustafa, Md Muziman Syah (2020)
Introduction: Sargassum polycystum (brown seaweeds) has been recognized as a potential source of natural antibacterial and antimicrobial compounds. It has been used in many applications and products as they possess interesting biological activities that give benefit to the dental and medical area. Aims: The objectives of this study were to determine the growth curve of Streptococcus mutans and Lactobacillus casei, and also to determine minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) value of Sargassum polycystum extract against Streptococcus mutans and Lactobacillus casei. Materials and methods: The growth of both bacteria were studied by growth curve analysis. Besides that, the antibacterial activity of Sargassum polycystum ethanol extracts against two oral cariogenic bacteria were examined using broth dilution method. The bioactivity of the seaweed extract was studied by finding the MIC and MBC value. Results: The time taken for the Streptococcus mutans and Lactobacillus casei to achieve exponential phase during growth is 4 and 5 hours respectively. MIC values of ethanol extracts of Sargassum polycystum in different concentration against Streptococcus mutans and Lactobacillus casei were unreliable because the presence of fungus (white-precipitate) at all 96-well plates including the positive and negative control. As there was no MIC value, partial inhibition was determined by calculating the optical density. Therefore, MBC analysis was unable to carry out because the MIC values were unreliable. Conclusion: The ethanol extract of Sargassum polycystum used in this study show partial bacterial inhibition against pathogens used. Therefore, the same study by using different type of solvent are recommended to be carried out in the future.